1993
DOI: 10.1016/s0886-3350(13)80011-9
|View full text |Cite
|
Sign up to set email alerts
|

Astigmatism after phacoemulsification with posterior chamber lens implantation: Small incision technique with fibrin adhesive for wound closure

Abstract: The scleral pocket technique has dramatically changed wound closure after phacoemulsification with implantation of a posterior chamber lens. The use of single-stitch technique and wound closure by fibrin adhesive is now possible. We conducted a comparative study of 385 consecutive patients; 167 received only fibrin glue for wound closure and 218 had the single-stitch procedure. No complications were observed in either group. Surgically induced astigmatism was smaller in the fibrin group (vector analysis: 0.80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…Buschmann (1986) had shown that fibrin could be used to stop perforation of the anterior capsule of the lens in order to avoid opacification. Mester et al (1993) used fibrin adhesive for wound closure to reinforce the wound, thus preventing postoperative against the rule astigmatism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buschmann (1986) had shown that fibrin could be used to stop perforation of the anterior capsule of the lens in order to avoid opacification. Mester et al (1993) used fibrin adhesive for wound closure to reinforce the wound, thus preventing postoperative against the rule astigmatism.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also used in a similar way in neurosurgical (Sawamura et al 1999), otolaryngological operations (Silberstein et al 1988), in vitro fertilization (Feichtinger et al 1990) and other microsurgery (Zauberman & Hemo 1988). In ophthalmology it has been used as an alternative to suturing for conjunctival closure following strabismus surgery (Biender & Rosenthal 1996), in the management of fornix‐based conjunctival wound leaks after trabeculectomy (Asrani & Wilensky 1996) and to prevent postoperative against the rule astigmatism after phacoemulsification (Mester et al 1993). It has also been used successfully in the closure of corneal perforations and descemetocoeles (Lagoutte et al 1989), to prevent bleeding and induce permanent conjunctival attachment in ocular surgery, reattachment of extraocular muscles (Spierer et al 1997) and many other ophthalmic procedures.…”
mentioning
confidence: 99%
“…[118] It has also been used for the prevention of post operative astigmatism and to seal the wound in small incision cataract surgery. [119120] Recently, the glue is being used to fix the haptics of IOL to the tissue in place of sutures. [121]…”
Section: Fibrin Glue In Ophthalmologymentioning
confidence: 99%
“…FG has been used in many surgical areas as topical hemostat, sealant, and tissue adhesive. FG is used in ophthalmology in vitreo-retinal surgery (full-thickness macular hole closure), 9 for conjunctival sealing in sutureless surgery, 10 closing incisions in cataract surgery, 11 and for bleb leakage in glaucoma surgery. 12 However, popularly, FG is used in pterygium surgery 13 and corneal surgery.…”
Section: Discussionmentioning
confidence: 99%